Clinical outcomes of esophageal squamous cell carcinoma in patients aged over 80 years - Dae Gon Ryu; Cheol Woong Choi; Su Jin Kim; Su Bum Park; Jin Ook Jang; Bong Soo Son (The Korean Journal of Internal Medicine)
Background/Aims The clinical outcomes and optimal treatment of esophageal squamous cell carcinoma (ESCC) in elderly patients are unclear. This study aimed to assess the clinical outcomes of ESCC in patients aged ≥ 80 years. Methods Medical records of patients diagnosed with ESCC between December 2008 and February 2024 were retrospectively reviewed. In total, 479 patients with ESCC were included and divided into the elderly (n = 52) and younger (n = 427) groups based on age. The clinical outcomes and survival rates, according to treatment, were compared between the two groups. Results The median ages of the two groups were 82 years (range, 80–95 yr) and 66 years (41–79 yr). The overall survival was slightly lower in the elderly group; however, no statistical significance (hazard ratio [HR] 1.27, 95% confidence interval [CI] 0.85–1.91; p = 0.238) was observed. No differences were observed in the outcomes or survival between the two groups according to the treatment method (surgery, chemoradiotherapy or radiotherapy alone, and endoscopic resection). The elderly group was more likely to receive no treatment for cancer (30.8% vs. 13.6%, p = 0.002) than the younger group. However, when there was no treatment for cancer in the elderly group, survival was significantly lower than when treatment was administered (HR 0.08, 95% CI 0.03–020; p < 0.001). Conclusions In patients with ESCC aged ≥ 80 years, active cancer treatment was beneficial, and the results did not differ from those of younger patients.